The effects of polymorphic characters in the phylogeny of the clade Cerdocyon + Atelocynus + Lycalopex (Mammalia, Carnivora, Canidae, Cerdocyonina) based on morphological characters - Leila Alessandra Martins Birkenhead (2019)
The phylogeny of Canidae has been inferred by many authors using different types of data. There is a consensus among molecular and combined phylogenies that the South American canids, a clade named Cerdocyonina, are monophyletic and divided in two major clades which are Chrysocyon + Speothos and Cerdocyon + Atelocynus + Lycalopex. The clade Cerdocyon + Atelocynus + Lycalopex has 8 species and the relationships among them are contradictory in both molecular and combined phylogenies. In the morphological phylogenies the incongruence within this clade is even greater. The presence of polymorphism in datasets, molecular and morphological, has instigated authors to create different coding methods. Since the report of polymorphism within Canidae is recent, different coding methods have not been tested with this data. This study aims to evaluate how different coding methods affects the phylogeny of the clade Cerdocyon + Atelocynus + Lycalopex. Our morphological dataset was coded by six coding methods and we compared the results to a molecular tree we generated based in sequences downloaded from Genbank. We also proposed a new coding method named Frequency-as-continuous. We obtained the largest sampling for the clade Cerdocyon + Atelocynus + Lycalopex ever assembled. The percentage of polymorphic entries in our dataset was higher than any other matrix. We did not recover a tree that had 100% similarity to the molecular tree. The topologies of the trees obtained by the matrices coded by the Frequency-bins and Frequency-as-continuous methods were similar. The trees which were most similar to the molecular tree were obtained from the matrices coded with the Polymorphic and the Frequency-bins methods respectively. Sample size affects the coding of polymorphism. We presumed the incongruence observed between phylogenies for the study group, which used morphological characters, could be linked to the high polymorphism present in the clade. We recommend using states frequencies as a guide to code any matrix because it reduces subjectiveness when coding.